(untitled) (Malaysian Journal of Learning and Instruction, 2025)
Purpose – This Q methodology study explores teachers’ views on using a digital badge system in two private schools. It aims to understand how teachers interpret, use, and value this system for personalising their professional development and validating skills from informal learning. The research seeks to identify factors influencing the acceptance and integration of digital badge systems in private schools. Methodology – The study used Q methodology, combining qualitative and quantitative methods to explore subjectivity. Thirty teachers from two private schools participated in professional development using a digital badge system. They ranked statements about the system on a scale from -4 (most disagreement) to +4 (most agreement) to identify features that would encourage acceptance. After ranking, teachers completed an open-ended questionnaire designed to obtain respondents’ personal insights. Principal component analysis was conducted on the rankings to identify factors related to acceptance. These factors, representing different opinion clusters, were analysed with the questionnaire responses and demographic data for a comprehensive understanding. Findings – Three distinct factors emerged from the analysis, highlighting the varied expectations of private school teachers. Factor 1, “Empowered Professional Development,” focused on giving teachers a sense of empowerment over their growth. Factor 2, “Rigorous and Flexible Professional Development,” emphasized the need for challenging yet flexible learning experiences. Factor 3, “Personalised Career Advancement,” prioritised individual career growth. Together, these factors represented the teachers’ diverse views on accepting a digital badge system for professional development. Significance – These findings offer insights into teachers’ diverse expectations and needs, helping to create a tailored and effective digital badge systems that private school teachers are more likely to embrace.